Phytochemical profiling, in vitro biological activity, docking studies, and cytotoxicity assessments of Rondeletia odorata Jacquin: An unexplored plant of the coffee family - Khursheed, Anjum; Ahmad, Saeed; Saleem, Muhammad; Khan, Kashif-ur-Rehman; Khan, Jallat; Orhan, Ilkay Erdogan; Abaci, Nurten; Imran, Muhammad; Tauseef, Saba; Uddin, Reaz; Yawer, Mirza Arfan; Tousif, Muhammad Imran; et al. (Frontiers in Chemistry, 2022)
Rondeletia odorata Jacquin is a flowering plant that belongs to the coffee family. As a rich source of polyphenols with significant antioxidant potential, R. odorata may have health benefits. Therefore, in the current work, ethanolic extract of aerial parts and its n-hexane, ethyl acetate, and n-butanol soluble fractions were analyzed for their antioxidant potential and various enzyme inhibition properties. The total phenolic and flavonoid contents of the crude ethanol extract (ROE) and its n-hexane (ROH), ethyl acetate (ROEA), and n-butanol (ROB) fractions were determined spectrophotometrically, while metabolic profiling was established through UHPLC-MS analysis, which revealed the presence of 58 phytochemicals. Total phenolic and flavonoid contents of ROE extract were measured as 51.92 mg GA.Eq./g of dry extract and 52.35 mg Qu.Eq./g of the dry extract, respectively. In the DPPH radical scavenging activity assay, ROE and ROEA showed the highest potential with values of 62.13 ± 0.62 and 76.31% ± 1.86%, respectively, comparable to quercetin (80.89% ± 0.54%). Similarly, in the FRAP assay, the same pattern of the activity was observed with ROE and ROEA, which displayed absorbance values of 1.32 ± 0.01 and 0.80 ± 0.02 at 700 nm, respectively, which are comparable (1.76 ± 0.02) with the reference compound quercetin, whereas the ROH showed maximum metal-chelating capacity (62.61% ± 1.01%) among all extracts and fractions. Antibacterial activity assay indicated that the ROEA fraction was the most active against Serratia marcescens, Stenotrophomonas maltophilia, Bacillus subtilis, Klebsiella pneumonia, and Staphylococcus aureus, while the rest of the fractions showed good to moderate activity. Enzyme inhibition assays showed that ROEA fraction exhibited the highest activity with IC50 values of 2.78 ± 0.42 and 3.95 ± 0.13 mg/mL against urease and carbonic anhydrase (CA), respectively. Furthermore, the docking studies of some of the major compounds identified in the extract revealed a strong correlation with their inhibitory activity. All extracts and fractions were also tested for their thrombolytic activity, and the ROB fraction showed a notable potential. Antiviral assay led to remarkable outcomes. Thus, it can be inferred that aerial parts of R. odorata are potential sources of bioactive components with several significant pharmacological activities.